Development and investigation on elastic plastic fracture analysis of Al6082 reinforced alumina/aluminium silicate MMCs using Taguchi approach. (2020) - Puneeth, N.; Satheesh, J.; Naveen, G.J.; Mohan, N.; Bhandari, Litton; Kiran, G.
Abstract: Aluminium metal matrix composite is widely used engineering material and not yet completely understood their dynamic response. Before using any material for application in critical industries like automobile, aerospace it is important to fully characterize the material properties. In the present study, the aim is to determine the elastic-plastic fracture toughness of AMC's by experimental methodology. Hence, the aluminium metal matrix composites were developed by combining the desirable attributes of metals and ceramics. In this work hybrid Al-based Al2 O3 /Al2 SiO5 reinforced composites are developed by incorporating Taguchi method in order to study the effect of different input process parameters namely wt% of Al2 O3 and Al2 SiO3, stirring time and stirring speed. The AMC's were fabricated by stir casting technique by varying three parameters i.e. wt% of Al2 O3 (4%, 8%, 12%), stir speed (150, 200, 250 rpm) and stir time (4, 8, 12 min). The tensile strength, impact strength, hardness and J integral test were conducted. The single edge notch (SENB) type geometry was used for mode I fracture testing. Taguchi method was successful in predicting the most influencing parameter on the composite properties by employing the ANOVA technique. It was also found that wt% of Al2 O3 is the most influencing process parameter on various properties of developed composites. The microscopic examination of developed composites was done to confirm the distribution of reinforcement particles in the Al matrix and fractography to study the material's behavior.